Healthcare resource consumption and cost of care among patients with polycystic kidney disease in Italy - Degli Esposti L; Veronesi C; Perrone V; Buda S; Santoro A (Dove Medical Press, 2017)
Luca Degli Esposti,1 Chiara Veronesi,1 Valentina Perrone,1 Stefano Buda,1 Antonio Santoro2 1Clicon S.r.l. Health, Economics & Outcomes Research, Ravenna, Italy; 2Department of Nephrology and Dialysis, Policlinico S. Orsola-Malpighi, Bologna, Italy Objective: The aim of this study was to assess healthcare resource consumption and its associated costs among patients with polycystic kidney disease (PKD) in a real-world setting.Methods: An observational retrospective cohort analysis was conducted using data from the administrative databases of four Italian local health units. Data for patients who were diagnosed with PKD during the inclusion period (January 1, 2010 to December 31, 2012) were extracted. The date on which a patient’s first PKD hospitalization occurred during the inclusion period was defined as the index date (ID), and the ID was defined as the date of the first dialysis treatment recorded during the inclusion period for patients undergoing dialysis. Data regarding the clinical characteristics of patients included in the study during the 12 months prior to the ID (pre-ID; characterization period) were collected. All patients were then followed up for the 12 months following the ID (post-ID; follow-up period). Healthcare consumption and its associated costs were analyzed during the follow-up period. All costs are reported in euros (€).Results: A total of 1,123 patients with PKD were included in this study, 61.9% of whom were male; the mean age of the patients was 57.7±24.5 years. At diagnosis, 11.2% and 1.1% of patients were affected by the dominant and recessive forms of PKD, respectively. Approximately 8% of the included patients were undergoing dialysis at ID (baseline). The incidence of dialysis was fourfold greater among patients with autosomal-dominant PKD (ADPKD) than among the total cohort (33.3% compared with an overall 8.3%). During the follow-up period, the average annual rates of healthcare resource consumption were greater among dialyzed than non-dialyzed patients. The average healthcare expenditures were €45,059.62 and €3,913.89 (p<0.001) per year for dialyzed and non-dialyzed PDK patients, respectively. Our findings suggest that in the real-world Italian context, consumption of healthcare among patients with PKD has increased at dialysis initiation due to the cost of outpatient specialist healthcare services as well as other costs. Research on the prevention of PKD-related complications and disease progression may help to facilitate a decrease in the costs associated with this condition. Keywords: polycystic kidney disease; autosomal-dominant polycystic kidney disease; autosomal-recessive polycystic kidney disease; real-world setting